2016
DOI: 10.1021/acs.jpcc.6b00867
|View full text |Cite
|
Sign up to set email alerts
|

Illuminating Excitonic Structure in Ion-Dependent Porphyrin Aggregates with Solution Phase and Single-Particle Resonance Raman Spectroscopy

Abstract: Self-assembled, excitonically coupled aggregates of 5,10,15,20-tetrakis(4-sulfonatophenyl)porphyrin (TSPP) prepared in aqueous LiCl, NaCl, KCl, CsCl, and HCl were studied with solution phase and single-particle resonance Raman (RR) spectroscopy. Solution phase excitation profiles are sharply peaked at 488.0 nm excitation for samples in HCl, LiCl, and CsCl, which show narrow J-bands in the corresponding absorption spectra, but more gently peaked for those induced by NaCl or KCl, which show broader absorption J-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 59 publications
(108 reference statements)
1
8
0
Order By: Relevance
“…However, the stereoselective effect of chiral co-solutes was found by the same authors on the aggregation behavior of porphyrin-based ionic liquids in acidic chlorinated solvents [58], as demonstrated by the fact that in the presence of a specific enantiomer of added R- or S-camphorsulfonic acid (CSA) acting as a chiral template, CD spectral features appear, with specific positive or negative signs depending on the selected CSA. The effect of the nature of alkali metal cations on the aggregation of the paradigmatic TPPS has been studied by Leishman and McHale [59], who pointed out differences in the morphology of the aggregates in the presence of MCl species (M = H + ; Li + ; Na + ; K + ; and Cs + ). Spectroscopic studies based on electronic absorption, resonance light scattering, and resonance Raman spectroscopy as well as imaging data, revealed a complex nanotubular morphology of the aggregates, whose intimate structures are environment-dependent.…”
Section: Effects Of Chemical External Stimulimentioning
confidence: 99%
“…However, the stereoselective effect of chiral co-solutes was found by the same authors on the aggregation behavior of porphyrin-based ionic liquids in acidic chlorinated solvents [58], as demonstrated by the fact that in the presence of a specific enantiomer of added R- or S-camphorsulfonic acid (CSA) acting as a chiral template, CD spectral features appear, with specific positive or negative signs depending on the selected CSA. The effect of the nature of alkali metal cations on the aggregation of the paradigmatic TPPS has been studied by Leishman and McHale [59], who pointed out differences in the morphology of the aggregates in the presence of MCl species (M = H + ; Li + ; Na + ; K + ; and Cs + ). Spectroscopic studies based on electronic absorption, resonance light scattering, and resonance Raman spectroscopy as well as imaging data, revealed a complex nanotubular morphology of the aggregates, whose intimate structures are environment-dependent.…”
Section: Effects Of Chemical External Stimulimentioning
confidence: 99%
“…11,18,27−30 We recently reported counteriondependent variations in TSPP aggregate morphology, with corresponding variations in absorption, RLS, and RR spectra. 13,14 We attributed these variations to weak excitonic coupling between bundled nanotubes and to different degrees of disorder in bundling and in transition dipole moment orientations within nanotubes. NaCl and KCl promoted bundling of nanotubes.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Self-assembled 5,10,15,20-tetrakis­(4-sulfonato­phenyl)­porphyrin (TSPP) aggregates are such a system and have the added benefit of being well-characterized in reference conditions (aqueous HCl at concentration ≳0.1 M). In recent work, we correlated counterion-dependent morphologies of TSPP aggregates with variations in excitonic absorption and resonance light scattering (RLS) spectral features . From resonance Raman (RR) spectroscopy, we identified effects of nanotube bundling and disorder on the relative strengths of transitions of differing polarization and coupling between such states, both in solution and in individual aggregates . Here, we examine aggregates prepared in acidified alcohols to explore other dimensions of our general hypothesis that solution environment shapes aggregate morphology, which in turn determines excitonic properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this framework, it has been reported that self-assembly of monodisperse gold colloid particles into monolayers on polymer-coated substrates produces highly reproducible macroscopic surfaces active for surface-enhanced Raman scattering (SERS) [31]. In fact, many spectroscopic studies on the interaction of AuNPs with porphyrins and their aggregates in solution and on surfaces have been reported [32,33,34,35,36]. In this particular area, our interest has focused on the J-aggregates of tetrakis(4-sulfonatophenyl)porphyrin (TPPS) [37,38,39,40,41,42].…”
Section: Introductionmentioning
confidence: 99%